Cover Feature: Syntheses of Bis‐Triazole Linked Carbohydrate Based Macrocycles and Their Applications for Accelerating Copper Sulfate Mediated Click Reaction (Eur. J. Org. Chem. 6/2019). Issue 6 (5th February 2019) - Chen, Anji; Samankumara, Lalith P.; Dodlapati, Sanjeeva; Wang, Dan; Adhikari, Surya; Wang, Guijun
Abstract : The Cover Feature the structure of an N ‐acetyl glucosamine based macrocycle containing two triazoles. The macrocycle and seven analogs were synthesized through CuI catalyzed cycloaddition reactions. The macrocycles showed remarkable rate acceleration for CuSO4 mediated azide and alkyne cycloaddition reactions in aqueous solutions. More information can be found in the Communication by G. Wang et al.